Revisão taxonômica de Rhamdia Bleeker, 1858, da bacia do río de La Plata, com a redescrição de Rhamdia quelen (Quoy & Gaimard, 1824). - Souza, Fagner de (2017)
Rhamdia Bleeker, 1858, is a genus that belongs to the Heptapteridae, whose species are distributed from Argentina to central Mexico, with about 24 valid species. In the Río de La Plata Basin three species co-occur, from these Rhamdia quelen (Quoy & Gaimard, 1824) is the most taxonomically problematic and it has an extensive list of synonyms. This species is considered a key species to solve several taxonomic problems in Rhamdia. Recent papers comment about the validation of some species in this basin and question the taxonomic status of several R. quelen synonyms. We reviewed the species of the genus distributed in the Río de La Plata Basin based on the original descriptions of both valid and synonym species and on materials from coastal, Amazonian and La Plata basins. In addition, it was proposed a redescription of R. quelen analyzing materials from the type-locality and from other basins (including the Neotype locality). For that, it was performed an analysis of external morphological characters with traditional, additional and truss network measurements, comparing several populations and species. We found that R. quelen is restricted to Brazilian coastal basins, from the rio São Francisco to the rio Paraíba do Sul. Also, it was revealed that the genus possesses three valid species in the Río de La Plata Basin and we removed Rhamdia sapo (Valenciennes, 1835) from the synonymy of the R. quelen.